Lysophosphatidic Acid Receptors: Biochemical and Clinical Implications in Different Diseases - Xiang, Hongjiao (J Cancer, 2020)
Lysophosphatidic acid (LPA, 1-acyl-2-hemolytic-sn-glycerol-3-phosphate) extracted from membrane phospholipid is a kind of simple bioactive glycophospholipid, which has many biological functions such as stimulating cell multiplication, cytoskeleton recombination, cell survival, drug-fast, synthesis of DNA and ion transport. Current studies have shown that six G-coupled protein receptors (LPAR1-6) can be activated by LPA. They stimulate a variety of signal transduction pathways through heterotrimeric G-proteins (such as Gα12/13, Gαq/11, Gαi/o and GαS). LPA and its receptors play vital roles in cancers, nervous system diseases, cardiovascular diseases, liver diseases, metabolic diseases, etc. In this article, we discussed the structure of LPA receptors and elucidated their functions in various diseases, in order to better understand them and point out new therapeutic schemes for them.